Network layer protocol architecture for many-nets internetworking - Guangpeng LI; Sheng JIANG; Chuang WANG (Dianxin kexue)
Based on the analysis of the evolution history of existing network protocol technologies,the innovative guiding principles applicable to the future data network unified protocol system was proposed.By dividing the nature of network functions into the connections between network elements,five areas of protocol innovation such as data plane,control plane,user plane,management control and intrinsic network security were proposed.The implementation and application of the protocol system in many heterogeneous scenario were analyzed.Finally,the rationality of the protocol innovation guidelines was verified by analyzing the protocol innovation process in deterministic network forwarding technology and intrinsic security network technology.